Polymorphs with Remarkably Distinct Physical and/or Chemical Properties. Issue 1 (27th September 2022) - Saha, Binoy K.; Nath, Naba K.; Thakuria, Ranjit
Abstract: Polymorphism in crystals is known since 1822 and the credit goes to Mitscherlich who realized the existence of different crystal structures of the same compound while working with some arsenate and phosphate salts. Later on, this phenomenon was observed also in organic crystals. With the advent of different technologies, especially the easy availability of single crystal XRD instruments, polymorphism in crystals has become a common phenomenon. Almost 37 % of compounds (single component) are polymorphic to date. As the energies of the different polymorphic forms are very close to each other, small changes in crystallization conditions might lead to different polymorphic structures. As a result, sometimes it is difficult to control polymorphism. For this reason, it is considered to be a nuisance to crystal engineering. It has been realized that the property of a material depends not only on the molecular structure but also on its crystal structure. Therefore, it is not only of interest to academia but also has widespread applications in the materials science as well as pharmaceutical industries. In this review, we have discussed polymorphism which causes significant changes in materials properties in different fields of solid‐state science, such as electrical, magnetic, SHG, thermal expansion, mechanical, luminescence, color, and pharmaceutical. Therefore, this review will interest researchers from supramolecular chemistry, materials science as well as medicinal chemistry. Abstract : Polymorphism in organic crystals and its roles in different areas of materials sciences and pharmaceuticals have been discussed.